Ardoise, extraction et fabrication, planche - Slate extraction... - EN NOIR & BLANC (Wikimedia Commons, 2011)
Notice iconographique issue de Wikimedia Commons. Titre: Ardoise, extraction et fabrication, planche - Slate extraction, historical, in France, plate with line illustrations, etc. - Public domain illustration from Larousse du XXème siècle 1932. Ardoise, extraction et fabrication, planche - Slate extraction, historical, in France, plate with line illustrations, etc. - Public domain illustration from Larousse du XXème siècle 1932. Slate is a fine-grained, foliated, homogeneous metamorphic rock derived from an original shale-type sedimentary rock composed of clay or volcanic ash through low-grade regional metamorphism. Éditions Larousse is a French publishing house specialising in reference works such as dictionaries. It was founded by Pierre Larousse and its best-known work is the Petit Larousse.
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie